Interferon and autoantigens: intersection in autoimmunity - Antiochos, Brendan; Casciola-Rosen, Livia (Frontiers in Medicine, 2023)
Interferon (IFN) is a key component of the innate immune response. For reasons that remain incompletely understood, the IFN system is upregulated in several rheumatic diseases, particularly those that feature autoantibody production, such as SLE, Sjögren’s syndrome, myositis and systemic sclerosis. Interestingly, many of the autoantigens targeted in these diseases are components of the IFN system, representing IFN-stimulated genes (ISGs), pattern recognition receptors (PRRs), and modulators of the IFN response. In this review, we describe features of these IFN-linked proteins that may underlie their status as autoantigens. Note is also made of anti-IFN autoantibodies that have been described in immunodeficiency states.